Developing a method for process design using limited data : A Fischer-Tropsch synthesis case study - Mukoma, Peter (My University, 2008)
Most of the available tools and methods applied in the design of chemical processes are not effective at the critical early stages of design when the process data is very limited. Businesses are often under pressure to deliver products in shorter times and this in turn prevents the evaluation of options. Early identification of options will allow for the development of an experimental program that will support the design process. The main objective of this work is to apply the Process Synthesis approach to develop a structured method of designing a process using mostly qualitative information based on limited experimental data, prior experience, literature and assumptions. Fischer-Tropsch (FT) synthesis of hydrocarbons from syngas generated by reforming natural gas and/or coal has been used as a case study to illustrate this method. Simple calculations based on experimental data and basic thermodynamics have been used to generate some FT Synthesis flowsheet models. The evaluation of different flowsheet models was done using carbon efficiency as a measure of process efficiency. It was established that when choosing the optimal region for the operation and design of an FT Synthesis process, the influence of the system parameters must be well understood. This is only possible if the kinetics, reactor, and process design are done iteratively. It was recommend not to optimize the reactor independent of the process in which it is going to be used without understanding the impact of its operating conditions on the entire process. Operating an FT Synthesis process at low CO per-pass conversions was found to be more beneficial as this will avoid the generation of high amounts of methane which normally results in large recycles and compression costs. Whether the process is run as a once-through or recycle process, the trend should be to minimize the formation of lighter gases by obtaining high Alpha values because carbon efficiency increases with the increase in value. Experiments should be performed to obtain process operating conditions that will yield high values. However, if the aim is to maximize diesel production by hydrocracking long chain hydrocarbons (waxes), then an optimal value should be targeted to avoid the cost of hydrocracking these very heavy waxes. The choice of the syngas generation technology has a direct impact on the carbon efficiency of an FT synthesis plant. This study has established that running an FT synthesis process with syngas obtained by steam reforming of natural gas with CO2 addition can yield high carbon efficiencies especially in situations were CO2 is readily available. In FT synthesis, CO2 is normally produced during energy generation and its emission into the environment can be minimized by using it as feed during the steam reforming of natural gas to produce syngas.
Keywords: Fischer-Tropsch synthesis; Process Synthesis; carbon efficiency; Alpha value